Perencanaan PLTS Off-Grid Menggunakan HOMER pada Gedung Operasional BTP Kelas II Padang: Perencanaan PLTS Off-grid Menggunakan HOMER pada Gedung Operasional BTP Kelas II Padang - Zakki Ahmad Ulinnuha (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2026)
The increasing demand for electrical energy and the high dependence on fossil fuels encourage the use of sustainable renewable energy, especially solar energy. Padang Pariaman Regency has high solar energy potential with an average solar radiation of 4.62 kWh/m²/day, so the implementation of an off-grid Solar Power Plant (PLTS) system is the right solution to support energy independence and reduce carbon emissions. This study aims to analyze the planning of an off-grid PLTS system at the Operational Building of Balai Teknik Perkeretaapian (BTP) Kelas II Padang from technical and economic aspects and evaluate its investment feasibility. The research methods include literature studies, field observations, and collection of primary and secondary data in the form of electrical load profiles, solar radiation data, and PLTS component specifications, which are analyzed through manual calculations and simulations using HOMER (Hybrid Optimization Model for Multiple Energy Resources) software. The analysis results show that both methods produce relatively comparable system configurations. Technically, the off-grid solar power system is designed with a solar panel capacity of 39,4 kW based on manual calculations and 45,2 kW based on HOMER software simulations, both of which are capable of meeting daily energy needs of 169,5 kWh with the support of a battery capacity of ±340 kWh that provides autonomy time of up to 48 hours and an inverter capacity of 80 kW which is above the peak load of 52,245.50 W. From an economic aspect, manual calculations produce a Net Present Cost (NPC) value of IDR 1,606,156,628 with a Cost of Energy (COE) of IDR 1,327/kWh, while the HOMER simulation produces an NPC of IDR 1,624,727,000 with a COE of IDR 1,405/kWh. Both methods show a positive NPV value, a Profitability Index greater than one, and a Discounted Payback Period below the project life, so that the off-grid solar power system is declared technically and economically feasible.